2016
DOI: 10.1093/hmg/ddw212
|View full text |Cite
|
Sign up to set email alerts
|

An enhanced Q175 knock-in mouse model of Huntington disease with higher mutant huntingtin levels and accelerated disease phenotypes

Abstract: Huntington disease (HD) model mice with heterozygous knock-in (KI) of an expanded CAG tract in exon 1 of the mouse huntingtin (Htt) gene homolog genetically recapitulate the mutation that causes HD, and might be favoured for preclinical studies. However, historically these mice have failed to phenotypically recapitulate the human disease. Thus, homozygous KI mice, which lack wildtype Htt, and are much less relevant to human HD, have been used. The zQ175 model was the first KI mouse to exhibit significant HD-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
131
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(164 citation statements)
references
References 75 publications
26
131
0
Order By: Relevance
“…4P) in these mice compared with control groups (n = 6-16/equal sex ratio). But, while, the HD mice had no observable phenotype, consistent with a previous report (45), and acquired motor learning skills (rotarod) comparable to WT or Fmr1 +/mice, the Q175FDN-Het; Fmr1 +/mice showed a subtle defects to learn motor skills, compared to WT mice ( Fig. 4Q).…”
Section: Fmr1 Depletion In Hd Mice Show No Discernable Phenotype Butsupporting
confidence: 89%
See 1 more Smart Citation
“…4P) in these mice compared with control groups (n = 6-16/equal sex ratio). But, while, the HD mice had no observable phenotype, consistent with a previous report (45), and acquired motor learning skills (rotarod) comparable to WT or Fmr1 +/mice, the Q175FDN-Het; Fmr1 +/mice showed a subtle defects to learn motor skills, compared to WT mice ( Fig. 4Q).…”
Section: Fmr1 Depletion In Hd Mice Show No Discernable Phenotype Butsupporting
confidence: 89%
“…Next, we investigated how wtHtt and mHtt interacted with ribosomes in the HD mouse brain (zQ175DN) (45). As expected, the treatment of HD cortical brain lysate with EDTA, which disassembled the ribosomes (Fig.…”
Section: Mhtt Interacts Directly With Ribosomes In Vitro and To An Rnmentioning
confidence: 73%
“…The functional implications of this expanded, mutant huntingtin are not fully understood. Much of the existing research on HD cell biology in relevant neuronal cell types has been limited to primary post-mitotic neurons from murine brain tissue or transformed cell lines, which have several limitations, including the use of synthetically long CAG lengths in order to mimic human disease in mice [2][3][4][5][6][7][8][9][10][11][12][13][14][15] . These alleles actually genetically model juvenile or Westphal variant HD, which are not age-onset diseases.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In this regard, some publications in animal models and small HD human retrospective studies have reported a more aggressive HD progression and brain atrophy in homozygotes. 2,3 In contrast, other authors have reported an indistinguishable phenotype in HD homozygotes and heterozygotes. [4][5][6][7][8] Given these contradictory data and the sparse longitudinal information, we aimed to further investigate the clinical differences between HD homozygotes (with both alleles ≥36 CAG repeats) and heterozygotes (with one allele ≥36 CAG repeats) in terms of age at onset, phenotypic presentation, and disease progression.…”
mentioning
confidence: 87%